How to make friends with a ghost - Green, Rebecca 1986- (Tundra, 2017)
What do you do when you meet a ghost? One: Provide the ghost with some of its favorite snacks, like mud tarts and earwax truffles. Two: Tell your ghost bedtime stories (ghosts love to be read to). Three: Make sure no one mistakes your ghost for whipped cream or a marshmallow when you aren't looking! If you follow these few simple steps and the rest of the essential tips in How to Make Friends with a Ghost, you'll see how a ghost friend will lovingly grow up and grow old with you
Keywords: Ghosts / Fiction; Friendship / Fiction; Humorous stories; Ghost stories; Friendship / Juvenile fiction; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Paranormal, Occult & Supernatural; JUVENILE FICTION / Social Themes / Friendship; Friendship; Fiction; Humorous fiction; Juvenile works; Picture books; Humorous stories / Juvenile fiction; Bilderbuch